PENDEKATAN ADAPTIVE REUSE PADA BANGUNAN KOMERSIAL NON-CAGAR BUDAYA DI KOTA BANDUNG - Amelia, Kiki Putri (Narada : Jurnal Desain dan Seni, 2024)
Adaptive reuse, defined as the practice of repurposing old buildings by converting them to serve new functions, has become an increasingly common phenomenon in commercial building in Bandung. In the city of Bandung, the local government has established specific guidelines for the classification of cultural heritage buildings, meaning that not all old buildings are recognized as heritage assets. The phenomenon found in commercial buildings nowadays is the reuse of old buildings, with transformation of transforming them into new functions. One common approach is seen in heritage buildings, termed adaptive reuse, where transformations maintain conservation values and principles. Field observations show many non-heritage buildings applying some principles of adaptive reuse in their implementations. Adaptive reuse principles, aligned with decision considerations in implementation, are in line with the principles of transforming forms. Qualitative methods with case studies and data triangulation prove several points in adaptive reuse principles used in transforming old buildings into new ones that are not heritage buildings. Although historical value is not the main focus of these decisions, they refers more towards other aspects such as social, economic, and aesthetic values, which can be additional points in design that are not found in new building designs.